Globalization and regionalization in South America - Pinto Salazar, Héctor (2017)
Between 1980 and 1990 the evolution of the international trade was marked by the tension between two seemingly contradictory trends: of a side the increasing globalization of the trade and of other one a variety of governments constructing blocks: EU, NAPH-THA, MERCOSUR, UNASUR, Alliance of the Pacífico, ALBA. Here there is present the notion of a global regionalized economy. In case of Peru, with his classic pendularidad, it has turned to a scheme of liberal condition, similar to the 50s. The regime fujimorista destroyed the national system of planning and the capacity of the departments to formulate public policies. The globalization raises the whole process of resettling of the periphery of the company, with the controversial concept of unsuccessful conditions.